Characterizing the shallow structure with the multimodal dispersion curves and the body wave refraction traveltimes from deep seismic sounding data - Guo, Wenbin; Li, Zhengbo; Zhao, Shuai; Chen, Xiaofei (Frontiers in Earth Science, 2023)
Deep seismic sounding (DSS) profiles are one of the most powerful tools for detecting crustal structures, and they have been deployed worldwide. Generally, the analysis of DSS data mainly focuses on body waves, while the surface waves are considered noise. We suggest that the surface waves in DSS data can be used to constrain subsurface structures. In this study, we use a DSS profile in the Piedmont and Atlantic Coastal Plain as an example to present the usage of the DSS surface wave. Multimodal dispersion curves were extracted from the DSS data with the Frequency-Bessel transform method, and were used in Monte Carlo joint inversions with body wave refraction traveltimes to constrain the shallow structures. Through the inversion, a horizontal stratum on the surface was identified in the Piedmont, and a two-layer sedimentary structure was identified in the Atlantic Coastal Plain. Comparisons with existing studies verified the accuracy of the shallow structures obtained in this study, demonstrating that the shallow velocity structure could be well constrained with the additional constraints provided by the multimodal dispersion curves. Thus, we believe that further research on the surface waves recorded in DSS surveys is warranted.